Undergraduate Awareness and Perception on the Use of Digital Collaborative Tools in Facilitating Learning in Selected Universities within the Ilorin Metropolis - Kehinde Muritala Nuhu; Damilola Ashiat Abdulfatai; Amos Ochayi Onojah (Universitas Pendidikan Indonesia (UPI), 2021)
The study identified the Digital Collaborative Tools used for learning among undergraduates; (i) determined undergraduates’ awareness on the use of these tools for learning; (ii) ascertained undergraduates’ perception of their use for learning; (iii) identified challenges faced on the use of Digital Collaborative Tools for learning; (iv) ascertained coping strategies of integrating these tools for learning in Ilorin metropolis; and (v) examined the influence of gender on undergraduates’ awareness of Digital Collaborative Tools for learning in Ilorin metropolis. The research adopted a descriptive research design of the survey type. The population is comprised of all undergraduate students in the Ilorin metropolis. A stratified random sampling technique was used to select 200 students and a researcher-designed questionnaire was used to elicit objective responses from the subjects. Frequency counts, percentages, and mean scores were used to analyze the research questions while t-test and Analysis of Variance (ANOVA) were employed in testing the hypotheses. The findings of this study were that Digital Collaborative Tools were used for learning among undergraduates. The study recommended that male and female teachers are to redirect their focus on the utilization of digital collaborative tools for learning.